Provably efficient RL with Rich Observations via Latent State Decoding - Du, Simon; Krishnamurthy, Akshay; Jiang, Nan; Agarwal, Alekh; Dudík, Miro; Langford, John (International Conference on Machine Learning, 2019)
We study the exploration problem in episodic MDPs with rich observations generated from a small number of latent states. Under certain identifiability assumptions, we demonstrate how to estimate a mapping from the observations to latent states inductively through a sequence of regression and clustering steps—where previously decoded latent states provide labels for later regression problems—and use it to construct good exploration policies. We provide finite-sample guarantees on the quality of the learned state decoding function and exploration policies, and complement our theory with an empirical evaluation on a class of hard exploration problems. Our method exponentially improves over Q-learning with naïve exploration, even when Q-learning has cheating access to latent states.